HPV: from infection to cancer. (23rd November 2007) - Stanley, M.A.; Pett, M.R.; Coleman, N.
Abstract : Infection with HPV (human papillomavirus) 16 is the cause of 50% or more of cervical cancers in women. HPV16 infection, however, is very common in young sexually active women, but the majority mount an effective immune response and clear infection. Approx. 10% of individuals develop a persistent infection, and it is this cohort who are at risk of cancer progression, with the development of high-grade precursor lesions and eventually invasive carcinoma. Effective evasion of innate immune recognition seems to be the hallmark of HPV infections, since the infectious cycle is one in which viral replication and release is not associated with inflammation. Furthermore, HPV infections disrupt cytokine expression and signalling with the E6 and E7 oncoproteins particularly targeting the type I IFN (interferon) pathway. High doses of IFN can overcome the HPV-mediated abrogation of signalling, and this may be the basis for the therapeutic effects on HPV infections of immune-response modulators such as the imidazoquinolones that induce high levels of type I IFNs by activation of TLR (Toll-like receptor) 7. Using the unique W12 model of cervical carcinogenesis, some of these IFN-related interactions and their relevance in the selection of cells with integrated viral DNA in cancer progression have been investigated. Our data show that episome loss associated with induction of antiviral response genes is a key event in the spontaneous selection of cervical keratinocytes containing integrated HPV16. Exogenous IFN-β treatment of W12 keratinocytes in which the majority of the population contain episomes results only in the rapid emergence of IFN-resistant cells, loss of episome-containing cells and a selection of cells containing integrated HPV16 in which the expression of the transcriptional repressor E2 is down-regulated, but in which E6 and E7 are up-regulated.